INTEGRASI TEKNOLOGI ARTIFICIAL INTELLIGENCE DALAM ASESMEN FORMATIF UNTUK MENINGKATKAN PERSONALIZED LEARNING PADA PEMBELAJARAN MATEMATIKA KELAS XI DI MA NURUL ALI SECANG MAGELANG - Fina Umu Rif Athi; La Mochtar Unu; Urip Wahyudin; Untung Desy Purnamasari; Faraisha Syahryanna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the integration of Artificial Intelligence (AI) in formative assessment to enhance personalized learning in Grade XI mathematics at MA Nurul Ali Secang Magelang. The research addresses the limited effectiveness of conventional formative assessment, which often delays feedback and does not accommodate individual learning differences. The objective of this study was to determine whether AI-based formative assessment significantly improves students’ learning outcomes and supports adaptive learning processes. A quasi-experimental design with a non-equivalent control group was employed, involving two classes: an experimental group using AI-supported formative assessment and a control group applying conventional methods. Data were collected through pre-test and post-test instruments, questionnaires on personalized learning, and classroom observations. Statistical analysis using independent sample t-tests and normalized gain (N-Gain) scores indicated that the experimental group achieved significantly higher post-test results and moderate-to-high learning gains compared to the control group. The findings also revealed increased student engagement and more precise feedback mechanisms in the AI-supported classroom. The study concludes that integrating Artificial Intelligence into formative assessment effectively strengthens personalized learning and improves mathematics achievement, while repositioning teachers as data-informed facilitators in the learning process.